Left Atrial Dysfunction in Children with Repaired Pulmonary Artery Atresia with Ventricular Septal Defect: A Cardiovascular Magnetic Resonance Imaging Study - Yanyan Ma; Liwei Hu; Qian Wang; Aimin Sun; Rongzhen Ouyang; Jinglei Wang; Hao Zhang; Haibo Zhang; Chen Guo; Yumin Zhong (MDPI AG, 2022)
(1) Background: The left atrium (LA) is much more than a reservoir for left ventricular filling. The aim of this study was to assess the LA volume and function in patients with repaired pulmonary artery atresia with ventricular septal defect (rPA/VSD) using CMR. (2) Methods: 31 pediatric patients with rPA/VSD and 30 healthy controls were prospectively recruited. Left atrial ejection fraction (EF), strain and strain rate of three phases (reservoir, conduit, and pump) and left atrial volume were measured with cardiac function analysis software. (3) Results: Patients with rPA/VSD had decreased maximal volume index (p = 0.008). Compared to controls, LA reservoir strain and strain rate, conduit strain and strain rate, booster pump strain rate, total EF and passive EF were significantly lower (p = 0.001, p < 0.001, p = 0.001, p = 0.02, p = 0.03, p < 0.001, p < 0.001); the patients with preserved but lower RVEF(<50%) had lower reservoir strain, reservoir strain rate and pump strain rate (p = 0.01, p = 0.02, p = 0.04, respectively) than the patients with higher RVEF (≥50%). (4) Conclusions: In patients with rPA/VSD, LA function was altered when biventricular EF was preserved, which may provide an early indication of left ventricular diastolic dysfunction. CMR can detect LA dysfunction at an early stage, even before LA enlargement.